Pengaruh Prosedur Kemudahan Menggadai Terhadap Keputusan Nasabah Dalam Menggadai Barang - Simanjuntak, Jontro (Universitas Pelita Harapan Medan, 2017)
The Effect of Easy Pawn Procedure to Customer Pawn Decision (Case Study of PT Pegadaian Batam Customer). To leave a valuable object in exchange for money and the object can be redeemed after a certain period of time is called mortgage. The study is aimed at determining the effect of easy pawn procedure to the customer's decision in pawning the goods. The framework of this study is, the influence of free variable to tied variable all together. The hypothesis proposed is easy pawn procedure has positive influence on the customer's decision in pawning goods. Collecting data process is conducted by using primary and secondary data through interview and questionnaire distribution. Data test is conducted by using validity test, reliability test, simple regression test and t test. Based on the results of the test the validity of research instruments, it can be concluded that of the 5 items of questions tested for the variable Procedure Ease (X), all items found to be valid. For reliability test, it is concluded that the question of the 5 items tested for customer decision variable (Y), all items declared valid. Based on multiple correlation significance test it is found that t_hitung> t_tabel, so there is a significant correlation between the ease of the procedure to the customer's pawning goods decision Keywords: Procedures Ease, and the Customer Decision